Prevalence of adverse childhood experiences (ACE) in the Czech Republic - Velemínský, Miloš; Dvořáčková, Olga; Samková, Jana; Rost, Michael; Sethi, Dinesh; Velemínský, Miloš (Child abuse & neglect, 2020)
A cross-sectional survey was undertaken to estimate the prevalence of child maltreatment and adverse childhood experiences in the Czech Republic, as data on these is scarce. The survey was conducted among 1760 randomly selected students from five Czech universities. Participants filled in the adverse childhood experiences survey instrument. The results showed that the prevalence of child maltreatment and other adverse childhood experiences is high: emotional abuse was reported by 20.7%, physical abuse by 17.1%, sexual abuse by 6.4%, and physical neglect by 8.0%. Household dysfunction was also high, with household street drug use reported by 4.9%, alcohol misuse by 15.3%, mental disorder by 13.4%, parental violence by 22.1% and parental separation by 23%. Thirty-eight per cent had not experienced any adverse childhood experience, while 9.9% reported experiencing four or more types of adverse childhood experiences. There was a significant association between adverse childhood experiences and health-harming behaviours such as suicide attempt, drug use, risky sexual behaviour and tobacco use. The findings suggest that there is a need to invest in prevention programmes.
Keywords: zdravotnické přehledy; průzkumy a dotazníky; Female; Prevalence; ženské pohlaví; průřezové studie; Surveys and Questionnaires; Health surveys; lidé; Violence prevention and control; fyzické násilí; Adverse Childhood Experiences; Health risk behaviour; Child neglect; prevalence; nepříznivé zkušenosti z dětství; Cross-Sectional Studies; Male; Czech Republic; Česká republika; Child abuse prevention and control; Health Surveys; mužské pohlaví; Physical Abuse; Humans